Mi Cristo Negro by Teresa Martínez de Varela: palimpsests between historical narrative and discursive religiosity - Sergio Daniel Rojas Sierra (Estudios de Teoría Literaria)
The article explores the work Mi Cristo negro (My Black Christ) by Colombian writer Teresa Martínez de Varela. It analyzes how the author uses elements of historical narrative and discursive religiosity to construct her story, with palimpsests, whose layers of meaning overlap and intertwine. The novel is presented as a space where the construction of historical memory and aspects of Catholic religiosity converge to propose an exemplary vindication of Manuel Saturio Valencia. Thus, hypertextual practices such as the transformation and imitation of style in the themes of textual structure, historical and religious substratum are examined. In doing so, it is proposed that the palimpsests that constitute the novel enrich the historical narrative through discursive religiosity. This invites us to think about the place of this work in the field of the Latin American historical novel of the twentieth century.